Bio-fabrication of multifunctional quasi-spherical green α-Fe2O3 nanostructures for paracetamol sensing and biomedical applications. Issue 23 (1st December 2021) - Navada, K. Meghana; Nagaraja, G.K.; D'Souza, Josline Neetha; Kouser, Sabia; Ravikumar, C.R.; Manasa, D.J.
Abstract: Green metal oxide nanostructures with various diverse properties are synthesized to find solutions to various problems arising in the field of medicine and technology. The present study includes cost-effective, eco-friendly synthesis of α-Fe2 O3 nanoparticles (ISD NPs), using varied volumes of extract of Scoparia dulsis as a reducing agent via Solution combustion synthesis. The extract influences the size, shape of quasi-spherical, bandgap positions, surface area to volume ratio of the nanoparticles prepared. The structural purity is ascertained via p -XRD studies, with nano regime size in the range of 27–37 nm. The optical energy gap (1.90–2.23 eV) and the mesoporous nature of the biogenic NPs have attributed by UV-DRS and surface area studies. The characterization findings reveal the "symbiotic association" of bio reducing agents and metal to influence the pronounced activity in biomedical and electrochemical studies. The controlled size and morphology give explicit results in in-vitro assays performed. The free radical scavenging hunt was maximum with DPPH inhibition of 71.88% and also exhibited depreciated cell viability of adenocarcinoma human alveolar basal epithelial cells to 39.88% with a lower IC50 value. The inherent stabilization behavior of ISD NPs towards human RBC's is appreciated (71.43%) owing to its bio-compatibility nature. The antidiabetic property via pancreatic α-amylase inhibition was in the range of 60–82%. The distinct electrochemical activities of the ISD NPs showed a higher proton diffusion coefficient (D) with 8.21 × 10 −6 cm 2 s −1, low charge resistance (85.27 Ω) and increased capacitance (5.3 × 10 −4  F). The electrochemical studies indicate that the ISD NPs as bio electrodes are a promising sensor for paracetamol drug detection. Graphical abstract: Image 1